2022
DOI: 10.3390/su14159214
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Urbanization and Eco-Environment in Hebei Province, China

Abstract: Understanding the complex interaction between urbanization and the eco-environment is necessary for rapid and quality urbanization, eco-environmental protection, and the harmonious coexistence of humans and nature within a region. Based on panel data from Hebei Province between 1985 and 2019, we suggested a symbiosis hypothesis of urbanization and the eco-environment (SHUE) and used the distance coordination coupling model, the Tapio decoupling model, and the symbiosis model to quantitatively determine the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…In our previous study, we confirmed the symbiosis hypothesis between urbanization and eco-environment, and quantitatively characterized the interdependence between the two using the symbiosis model, which revealed the interaction and reaction between urbanization and eco-environment [34]. Therefore, this study continues to use the symbiosis degree model to quantitatively measure the symbiosis of the simulation results between urbanization and eco-environment.…”
Section: Symbiosis Model Of Urbanization and Eco-environmentsupporting
confidence: 63%
See 2 more Smart Citations
“…In our previous study, we confirmed the symbiosis hypothesis between urbanization and eco-environment, and quantitatively characterized the interdependence between the two using the symbiosis model, which revealed the interaction and reaction between urbanization and eco-environment [34]. Therefore, this study continues to use the symbiosis degree model to quantitatively measure the symbiosis of the simulation results between urbanization and eco-environment.…”
Section: Symbiosis Model Of Urbanization and Eco-environmentsupporting
confidence: 63%
“…In our previous study, based on panel data from 1985 to 2019 in Hebei Province, we proposed and verified the symbiosis hypothesis between urbanization and the ecoenvironment, and constructed a quantitative study method system in order to reveal the interaction relationship between them from the two dimensions of coupling and decoupling [34]. To further investigate the possible future development trends and the main factors affecting the interaction between urbanization and the eco-environment in Hebei Province, this study constructs an SD model and simulates the short-and long-term development trends through multiple scenarios.…”
Section: Research On the Coordinated Development Of Urbanization And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, numerous scholars have extensively studied the relationship between ecological environment, biological population factors, and economic development in the process of urbanization. The majority of their conclusions tend to indicate that urbanization has negative impacts on ecological environment and biological populations, while simultaneously playing a promoting role in social and economic development [19][20][21][22][23][24] . However, there were also some scholars who held different opinions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the urbanization of the Huaihe Eco-economic Belt in recent years, economic conditions and infrastructure construction have achieved better results [7,8], but in the process, some of the environment may be destroyed and available resources reduced [9,10], which can seriously affect the sustainable development of the region. Therefore, the harmonious development of urbanization and eco-environment has become an important way and the core of modernisation and sustainable development of China [11][12][13]. In this context, exploring the coupled and coordinated development of urbanization and the eco-environment in the Huaihe Eco-economic Belt can provide a reference for the region to achieve high-quality and differentiated development.…”
Section: Introductionmentioning
confidence: 99%